Unexpected Dominance of Elusive Acidobacteria in Early Industrial Soft Coal Slags - Wegner, Carl-Eric; Liesack, Werner (Frontiers in Microbiology, 2017)
Acid mine drainage (AMD) and mine tailing environments are well-characterized ecosystems known to be dominated by organisms involved in iron- and sulfur-cycling. Here we examined the microbiology of industrial soft coal slags that originate from alum leaching, an ecosystem distantly related to AMD environments. Our study involved geochemical analyses, bacterial community proﬁling, and targeted metagenomics. The slags still contained high amounts of alum constituents (aluminium, sulfur), which mediated direct and indirect effects on bacterial community structure. Bacterial groups typically found in AMD systems and mine tailings were not present. Instead, the soft coal slags were dominated by uncharacterized groups of Acidobacteria (DA052 [subdivision 2], KF-JG30-18 [subdivision 13]), Actinobacteria (TM214), Alphaproteobacteria (DA111) and Chloroﬂexi (JG37-AG-4), which have previously been detected primarily in peatlands and uranium waste piles. Shotgun metagenomics allowed us to reconstruct 13 high-quality Acidobacteria draft genomes, of which two genomes could be directly linked to dominating groups (DA052, KF-JG30-18) by recovered 16S rRNA gene sequences. Comparative genomics revealed broad carbon utilization capabilities for these two groups of elusive Acidobacteria, including polysaccharide breakdown (cellulose, xylan) and the competence to metabolize C1 compounds (ribulose monophosphate pathway) and lignin derivatives (dye-decolorizing peroxidases). Equipped with a broad range of efﬂux systems for metal cations and xenobiotics, DA052 and KF-JG30-18 may have a competitive advantage over other bacterial groups in this unique habitat.